Role of cIAP1 and cIAP2 in Skeletal Muscle - Whitney, Rachael (Université d'Ottawa / University of Ottawa, 2022)
The cellular inhibitor of apoptosis 1 and 2 (cIAP1 and cIAP2) proteins are essential regulators of the classical and alternative NF-κB pathways. The NF-κB pathway has been shown to be an important regulator of myogenesis and plays a role in skeletal muscle disease, but the involvement of cIAP1 and cIAP2 has not been examined in healthy skeletal muscle. I sought to characterize skeletal muscle of the cIAP1-null and cIAP2-null mice. We show mice lacking cIAP1 exhibit decreased satellite cell numbers in the TA following cardiotoxin-induced injury and in the uninjured soleus muscle, suggesting cIAP1 may be important for satellite cell expansion. cIAP2 may play a role in fiber maintenance and homeostasis as we show cross- sectional are of cIAP2-null uninjured tibialis anterior fibers at 7 and 10 weeks of age were significantly smaller than wild-type fibers. Furthermore, cIAP1- and cIAP2-null mice subjected to in situ force experiments demonstrated altered twitch kinetics compared to wild-type controls in the soleus and EDL, suggesting fast and slow-twitch fibers are affected differently by loss of cIAP1 and cIAP2. Further work elucidating the downstream mechanisms by which cIAP1 and cIAP2 regulate skeletal muscle development and regeneration will be beneficial to the development of treatments for muscular disorders. In this regard, Smac mimetic compounds (SMCs) are small molecule inhibitors that target cIAP1/2 for degradation, thus provide a potential therapeutic treatment for muscular disorders.
Keywords: apoptosis; NF-kB; myogenesis; muscle; satellite cell; fibers